Pendidikan dalam Cengkraman Kapitalisme - Mir’atussolihah Mir’atussolihah; Novia Vanda Pratiwi; Annaj Mutsaqib; Syukron Makmun (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2023)
Education is one of the breaker ropes of poverty. But has every citizen received education to the highest level? What about the education for all program? The basic conception of educational equity aimed at equality in education and equity in education does not seem to go hand in hand and can even be said to be opposite each other in order to educate the nation's life. The principle of education for all that is often echoed is also still dealing with discrimination against society on the basis of class and status in obtaining justice and educational opportunities. Various assumptions are put forward starting from government policies which are considered to change frequently, public awareness of the importance of education is still not optimal, the process of providing education is felt to be too expensive, and on the other hand free education policy propaganda offers public wishful thinking which is sometimes not in line with the reality of the cost of education that must be paid. issued by society. This paper wants to discuss a bit of the conflict between free education policies and the practice of educational capitalism which is often found in the midst of globalization and amidst the demands of stakeholders for the importance of education.